AQuaos: spatial aquaculture decision support system using multi integrated open source GIS / Abdul Rauf Abdul Rasam … [et al.] - Abdul Rasam, Abdul Rauf; Ahmad Nazari, Nur Atirah; Zulkarnain, Nur Nabihah; Ruslan, Nurfadhilah; Jaini, Norajlin (Research Innovation Business Unit, 2014)
The development of the Malaysian aquaculture industry has grown rapidly in recent years. The challenges faced by the industry are the use of expertise to manage and guide aqua culturist particularly in managing database and application of communication online between the government and the fishery community. The aim of the study is to develop a prototype of a novel system for Malaysian fishery or the aqua cultural community using multi techniques, datasets and open source GIS (AQuos). The AQuos Version 1.1 was initially created based on real local problem situation which was implemented in 4 main stages. Firstly, primary and secondary data were collected in Selangor and from other related organisations. Then, geodatabase, data processing and data exploration were conducted using multi integrated open sources GIS. The potential areas for suitable sites for aquaculture were also determined using MCDM techniques. Lastly, the AQuos web-based system was designed and developed using Map Guide Software. This study found that the respondents from the related organisations agreed that the system was useful for local authorities and for efficient aquaculture database management and analysis.